Is neoadjuvant immunotherapy feasible for patients with dMMR/MSI−H locally advanced colorectal cancer? a retrospective study - Luo, Zhenkai; Wang, Danjun; Wang, Zhexue; Zhao, Hang; Xiang, Renshen (Frontiers in Immunology, 2025)
BackgroundNeoadjuvant immunotherapy has demonstrated satisfactory efficacy for high microsatellite instability/mismatch repair deficiency (dMMR/MSI-H) in locally advanced colorectal cancer (LACRC). This study aims to evaluate the safety and short-term efficacy of neoadjuvant immunotherapy for patients with LACRC.MethodsWe retrospectively analyzed patients with dMMR/MSI-H LACRC who received neoadjuvant immunotherapy at two Chinese medical centers. The primary outcome of the study was the pathological complete response (pCR) rate, while secondary endpoints included survival status, perioperative outcomes and safety profile.ResultsA total of 26 patients were included in the analysis, with a median age of 58 years (range: 33–78 years). All patients underwent radical surgery after completing neoadjuvant immunotherapy. All patients achieved R0 resection, and the pCR rate was 92.3% (24/26). Furthermore, all patients experienced downstaging (100%). Eight patients (30.8%) experienced immune-related adverse events (IRAEs), and five patients (19.2%) developed postoperative complications. The median follow-up duration was 19.0 months (range: 4.0-41.0 months). No patients died during the follow-up period, and no local recurrence or distant metastasis was observed.ConclusionNeoadjuvant immunotherapy appears to be a safe and effective treatment for patients with dMMR/MSI-H LACRC, offering a feasible and acceptable therapeutic regimen before surgery.